Our flesh is here but our soul stayed there: A qualitative study on resource loss due to war and displacement among internally-displaced women in the Republic of Georgia. (February 2016) - Seguin, Maureen; Lewis, Ruth; Amirejibi, Tinatin; Razmadze, Mariam; Makhashvili, Nino; Roberts, Bayard
Abstract: Losses experienced by conflict-affected civilians in low and middle income countries is a relatively unexplored area. The aim of our paper is to explore the concept of resource loss in the accounts of internally displaced women in Georgia. We use Hobfoll's Conservation of Resources (COR) theory to guide our approach by examining the loss of objects, personal characteristics, conditions, and energies . Semi-structured interviews were conducted on 42 purposively-selected Georgian women residing in internally displaced persons settlements during fieldwork in Georgia from December 2012 to February 2013. Line-by-line open-coding was conducted on translated and transcribed interviews using Nvivo. The conservation of resources theory was utilised to guide the 'mapping' of the relationships between losses which occurred in the post-conflict period. War-related trauma led to the loss of property, which caused the loss of livelihood and subsequent loss of social networks and mental and physical health. The mental and physical health losses, along with the loss of livelihood, constituted a loss spiral in which losses in one area perpetuated on-going losses in the other areas. Interventions at supporting livelihoods are needed in order to address the cascade of losses resulting from war. Highlights: Provides evidence on the long-term impacts of war and displacement on women. Presents the nuanced interactions between types of losses resulting from displacement. Uses Conservation of Resources theory to clarify loss experienced by displaced women.